1985
DOI: 10.1021/jf00064a004
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and nature of bound (nonextractable) residues of atrazine in a mineral soil nine years after the herbicide application

Abstract: Uniformly UC ring-labeled atrazine was applied to a mineral soil under field conditions. Nine years after application of the herbicide soil samples were collected for analysis. The soil contained about 50% UC residues in the bound (nonextractable) form. The bound 14C residues were distributed among the various soil humic fractions. In addition to the parent herbicide a considerable proportion of these residues was comprised of the hydroxy analogues of atrazine and their dealkylated products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
91
1
1

Year Published

1991
1991
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(104 citation statements)
references
References 12 publications
11
91
1
1
Order By: Relevance
“…The environmental behavior of atrazine by addition of organic amendments, like plant residues, or its mineralization during bioremediation, field application and agricultural use has been studied intensively (Alvey and Crowley, 1995;Barriuso and Houot, 1996;Silva et al, 2004). A number of studies have observed a so-called "bound residue" fraction of atrazine in soil (Capriel et al, 1985;Schiavon, 1988;Barriuso et al, 1991;Loiseau and Barriuso, 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The environmental behavior of atrazine by addition of organic amendments, like plant residues, or its mineralization during bioremediation, field application and agricultural use has been studied intensively (Alvey and Crowley, 1995;Barriuso and Houot, 1996;Silva et al, 2004). A number of studies have observed a so-called "bound residue" fraction of atrazine in soil (Capriel et al, 1985;Schiavon, 1988;Barriuso et al, 1991;Loiseau and Barriuso, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Even though atrazine forms soil-bound interfaces it is still unclear whether these bound residues are bioavailable or represent a potential risk for future groundwater contamination. Since atrazine was found in bound forms nine years after its application (Capriel et al, 1985), it can be assumed that this chemical compound is not excluded from environmental interaction even after long-term aging under outdoor conditions. Pignatello et al (1993) suggested that changing environmental dry-wet cycles may cause pulse inputs from resistant herbicide pools to subsurface layers, which might become crucial under changing environmental conditions.…”
Section: Introductionmentioning
confidence: 99%
“…However, undegraded atrazine residues remain in the soil for quite a long time due to the poor chemical reactivity of atrazine (Capriel et al, 1985), and from the soil they can reach waters and watering systems. Atrazine was also detected in maize (Norris and Fong, 1983), one of the constituents of the gilts feed mix.…”
Section: Discussionmentioning
confidence: 99%
“…Bound residues are associated with humic and clay fractions of the soil [24,25]. Apparently, when microbial activity creates anaerobic conditions, some bound atrazine is released.…”
Section: Fe and Mnmentioning
confidence: 99%